2020
DOI: 10.15294/jpfi.v16i1.23096
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Behavior of Learning and Student Achievement in Physics Subject

Abstract: Behavioral problems become special attention to learning. Some teachers confronted with a variety of student behaviors and varied learning outcomes. This research was aimed to determine the relationship between learning outcomes and student learning behavior with ranking score. A total of 91 of 10th-grade students with three different classes became respondents. The research was used Mixed methods with the sequential explanatory approach. Quantitative data were obtained by giving multiple-choice questions. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
1
6
0
1
Order By: Relevance
“…It is concluded from that those students' have this ability easily solve their problems. This problem-solving ability can helpful for students in their daily life problems as supported by (Azhary et al, 2020).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It is concluded from that those students' have this ability easily solve their problems. This problem-solving ability can helpful for students in their daily life problems as supported by (Azhary et al, 2020).…”
Section: Discussionmentioning
confidence: 97%
“…The findings highlight that a deficiency in conceptual knowledge leads to a decline in academic achievement, mirroring the conclusions drawn by Khan et al (2017) who also observed a direct relationship between these factors where an increase or decrease in one corresponds to a similar change in the other. If students' increase their concept learning ability they can became more efficient in solving the problems of physics as well as out of the prescribed syllabus (Azhary et al, 2020). There is positive effect of conceptual knowledge on students' concept learning capability (Ardianti, et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…A supportive learning atmosphere, teacher behavior, and various factors are essential for improving student outcomes. Behavioral problems should be addressed by teachers or psychologists to ensure positive learning behaviors (Azhary et al, 2020). The qualitative study by Akramy (2021) explores the impact of Outcome-Based Education (OBE) on student behavior in Afghanistan.…”
Section: Discussionmentioning
confidence: 99%
“…Also, their interest can establish their habits of mind which include critical thinking and self-regulation which are essential in the successful pursuit of Physics learning (Susilowati et al, 2019). Lastly, it does not only develop their attitude towards the subject but also their academic performance which is a reliable indicator of their academic success (Azhary et al, 2020).…”
Section: Introductionmentioning
confidence: 99%